2004
DOI: 10.1097/00126334-200404150-00005
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Resistant Variants That Evolve During Nonsuppressive Therapy Persist in HIV-1–Infected Peripheral Blood Mononuclear Cells After Long-Term Highly Active Antiretroviral Therapy

Abstract: The aim of this study was to determine whether drug-resistant virus persists in peripheral blood mononuclear cells (PBMCs) after long-term suppression of virus replication. Proviral DNA was extracted from the PBMCs of 11 patients on long-term highly active antiretroviral therapy (HAART). Genotyping of the reverse transcriptase (RT) and protease gene of several proviral variants was performed using limiting dilution polymerase chain reaction and single-copy sequencing. All patients were on successful HAART for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
41
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 22 publications
4
41
0
Order By: Relevance
“…Most of these discordances may be attributed to differences in the selection of the samples used for the evaluation. While plasma RNA represents the population of short-lived actively replicating virus, viral DNA from infected cells is composed of a heterogeneous mix of DNA from acutely infected, actively virus-producing cells as well as quiescent cells that form the viral reservoir (13,27,40). Due to the limited capacities of current population-based sequencing genotyping methods, minor variants can remain undetectable (38).…”
Section: Continued On Facing Pagementioning
confidence: 99%
See 1 more Smart Citation
“…Most of these discordances may be attributed to differences in the selection of the samples used for the evaluation. While plasma RNA represents the population of short-lived actively replicating virus, viral DNA from infected cells is composed of a heterogeneous mix of DNA from acutely infected, actively virus-producing cells as well as quiescent cells that form the viral reservoir (13,27,40). Due to the limited capacities of current population-based sequencing genotyping methods, minor variants can remain undetectable (38).…”
Section: Continued On Facing Pagementioning
confidence: 99%
“…Interruption of a failing regimen or a failing drug will result in an overgrowth of the drug-resistant variant by the more fit wild type (13,27,40). In the cellular reservoir on the other hand, the resistant strains will remain detectable for longer time.…”
Section: Continued On Facing Pagementioning
confidence: 99%
“…Since viruses can be continually deposited into the latent reservoir during periods of low-level viremia or during treatment failure and can exit the latent reservoir when their host cell is activated (10), latency provides a means for the archiving and reemergence of sequences representing the history of a patient's quasispecies. When drugresistant viruses are present, they are also archived in the latent reservoir (11)(12)(13)(14)(15). Since viral rebound from latently infected cells occurs upon treatment interruption or treatment failure (16), previously existing drug-resistant viruses that are present in the latent reservoir preclude patients from being treated with that drug or drug combination in the future.…”
mentioning
confidence: 99%
“…Recombination within individual patients has been documented in numerous studies (reviewed in reference 25), and recombination involving drug-resistant viruses provides a mechanism for the spread of drug resistance throughout a patient's quasispecies (28)(29)(30). Since the latent reservoir represents an archive of the history of a patient's quasispecies, including viruses with any previously existing drug resistance mutations (11)(12)(13)(14)(15), latent viruses represent an important source for the further generation of genetic diversity under selective pressure. This could occur following superinfection of a latently infected cell.…”
mentioning
confidence: 99%
“…The latent HIV-1 population stored in resting CD4 ϩ T cells is a diverse collection of archival viral species exhibiting various degrees of divergence from the most recent common ancestor (37,44,51,55,67). Longitudinal studies have demonstrated a lack of temporal structure and evolutionary change in the viral species residing in this reservoir in most patients with undetectable plasma HIV-1 RNA measurements (3,26,41,52,55,77).…”
mentioning
confidence: 99%